Analisis Persamaan Simultan Insider Ownership, Utang dan Kebijakan Deviden Beserta Faktor-Faktor yang mempengaruhinya. - Akmalia, Alien; Hindasah, Lela (Universitas Muhammadiyah Yogyakarta, 2010)
This study excamined the simultaneous between debt, dividend and insider ownership with the factors that have influence. This reaserch facused on non financial companies which is register in Indonesia Derivative Exchange (BEI), for 2002-2006, it report the financial data complately and publish on Indonesian Capital Market Directory (ICMD). Sample taking use purposive sampling method and bring 76 compaies as the result.This study use Two Stage Square (2SLS), because the identification of simultaneous equation must fulfill just identified criteria. The exogeneous variables that use in this study are debt, dividend and insider ownership. The endogenous variables that use in this study are business risk, profitability, investment, fixed assets, growth and size of the firm.The result of reasearch shows that on debt equastion : dividend, insider ownership, risk, profitability and fixed asset have sigificant influence to debt. On dividend equation: debt, insider ownership, risk, profitability, investment and growth have significant influence to devidend. On insider ownership equastion debt, dividend, risk, and size have significant influence to insider ownership.